CLIL: The approach for the future? - Jalo, Marcela Lilian (2014)
The aim of this article is to explore the potential of CLIL as a key approach in the future of English language teaching. Issues related to the different roles of teachers -including teacher training- and to the school specific subjects have been discussed . We have also focused our attention on the relationship between this approach and culture. The role of language in CLIL and the implementation of different modes of assessment are also mentioned. Material selection and adaptation is analysed in the light of CLIL ? principles. The analysis of these points leads us to provide a series of requisites which are to be met if we want the CLIL approach to improve out teaching practices and our students learning experiences